The women knowledge, attitude, and perceptions of pre-eclampsia and eclampsia in Madagascar - Romuald, Randriamahavonjy; Ratsiatosika, Tanjona A.; Martial, Rakotonirina A.; Lantonirina, Rainibarijaona A.; Ando-Miora, Rakotonirina; Rakotovao, Andrianampanalinarivo H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Preeclampsia is a complication of pregnancy responsible for high rates of morbidity and mortality, particularly in Africa and Madagascar. The objective of present study was to assess patients' knowledge, attitudes and beliefs about pre-eclampsia in Madagascar. Methods: This is an observational study on the knowledge, belief and attitudes of women seen at the Befelatanana Gynecology and Obstetrics Hospital and conducted by questionnaires from 1 December 2017 to 30 May 2018. Results: During the study period, 102 patients agreed to answer our questionnaire. Terminology exists in the local language to describe convulsions and hypertension, but there were no terms that are specific to pregnancy. More than half of our patients knew preeclampsia. In 41% of cases, patients attributed excessive salt intake as a cause of high blood pressure during pregnancy and in 20% secondary to stress. Headache was the best-known symptom of patients. Signs of danger such as epigastric pain, genital bleeding, visual disturbances, convulsions and decreased sensation of fetal movements are not well known to patients. One-third did not know it was lethal. Regarding fetal complications, the occurrence of fetal death in utero was the best known. The majority of patients were aware that blood pressure measurements and urine dipstick testing were mandatory during pregnancy follow-up. To prevent preeclampsia, 46.07% thought that reducing salt intake would reduce the occurrence of preeclampsia. Conclusions: Few patients are aware of preeclampsia, its danger signs and its complications, especially during prenatal consultation. This requires the improvement of knowledge of all health actor. Community health workers should receive basic and ongoing training to facilitate dialogue and information for pregnant and non-pregnant women in each society.